Aluminum-alloyed lightweight stainless steels strengthened by B2-(Ni, Fe)Al precipitates. (August 2021) - Harwarth, M.; Chen, G.; Rahimi, R.; Biermann, H.; Zargaran, A.; Duffy, M.; Zupan, M.; Mola, J.
Graphical abstract: Highlights: Ni addition enables microstructures from fully ferritic to martensitic-austenitic. Solute Al and Ni in martensite cause a pronounced age-hardening response. Age hardening arises from the formation of B2-(Ni, Fe)Al precipitates. Peak hardness is similar to maraging grade 300 and superior to PH stainless steels. B2 Formation in martensite is associated with heat release and a net contraction. Abstract: The age hardenability of Al-alloyed lightweight stainless steels with the base chemical composition Fe–10.5Cr–3Al (wt.%) and Ni concentrations in the range 3–15 wt.% was studied. Alloys containing 3% and 6% Ni exhibited almost fully ferritic matrix microstructures and a weak age hardening response. Alloys containing 9%, 12%, and 15% Ni, on the other hand, developed primarily martensitic microstructures. Differential scanning calorimetry measurements indicated the occurrence of an exothermic reaction in the approximate temperature range 375–625 °C. Dilatometry measurements indicated that the exothermic reaction was accompanied by a net contraction. Hardness measurements after aging for 5 min indicated significant hardening of alloys already at 350 °C due to the formation of B2-(Ni, Fe)Al intermetallic precipitates. The age hardening response was significantly superior to that of conventional precipitation-hardenable martensitic stainless steels. Tensile elongation in the aged condition was negatively influenced by the presence of soft ferrite regions. Processing conditions associated with a fully martensitic microstructure prior to aging are required to render a uniform age hardening response. Guidelines for the development of a new family of lightweight precipitation-hardenable steels with lower raw material costs and a higher corrosion resistance compared to the standard 18Ni maraging steels are provided.